Burn-Out Chez Le Personnel Soignant Des Unités De Soins Intensifs De L’hôpital Universitaire De Parakou Au Bénin - Tchaou Blaise Adelin; Djidonou Anselme; Tchegnonsi N’venonfon Charles Frédéric; Gbogblenou Gloria Todègnon Armistice; Gandaho Prosper (European Scientific Journal, ESJ, 2018)
The aim of the study was to identify Burn-out factors among caregivers in intensive care units in University Hospital of Parakou. We used a descriptive, analytical and correlational study with prospective data collection carried out over four months (March 1 to June 30, 2015) and 123 caregivers concerned consenting to the study. The Maslach Burn-out Inventory (MBI) was used for the assessment of burnout of the respondents. Among the 143 agents identified, 123of them (86%) consented to the survey. The average age of caregivers was 34.4 ± 9.3 years with a male predominance (56.9%). Seventy-six caregivers lived with a partner (61.8%) and 90.8% of them were monogamous. Seventy-one caregivers (57.7%) were not satisfied with their socio-economic situations and 88.7% of them associate secondary activities. Eighty eight caregivers (71.5%) were identified in their industry stressful conditions. The frequency of Burn-out was 68.3%. The occurrence of burn out was associated with sex (p = 0.001), type of family (p = 0.001), vocational qualification (p = 0.001) in the industry (p = 0 001), socio-economic conditions (p = 0.01), disease appeared in the exercise of the profession (p = 0.02), organizational factors (p = 0.001) and stressful conditions (p = 0.04). In conclusion we observe that the function nurse in the intensive care unit of the University Hospital of Parakou has a physical and mental hardship among caregivers inducing a high score of Burn-out, implementing an adapted prevention program is therefore necessary to lowering it.